WAVE RUN-UP ON ROCK SLOPES OF A COASTAL STRUCTURE - Mustafid . (JOURNAL OF COASTAL DEVELOPMENT, 2001)
A wave runrup height on a coastal structure with sloping face is one ofthe considerations in the planning and design of sea—walLs or brealcwaters. In this paper, a wave run—up height on rock slopes of a coastal structure is presented using the empirical approach based on incident waves entering coastal structure. A height and increasing level of wave run-up hom incident wave amplitude are presented on rock slopes of a coastal structure with various angle of structure slopes and various water depths. The influence of incident wave height and wave period on the wave run-up height are described through the correlation analysis, and the probability distribution of wave run-up height is described as a Weibull distribution.